1987
DOI: 10.1038/clpt.1987.193
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine, a new anticonvulsant: Pharmacokinetics in normal humans

Abstract: The pharmacokinetics of lamotrigine, a new anticonvulsant, were studied in three studies in normal volunteers. In the first study, five subjects received oral doses of lamotrigine up to 240 mg. A linear relationship was observed between dose administration and both peak drug concentration and AUC. In a second study 10 subjects received 120 mg lamotrigine and the mean (+/- SD) of the elimination half-life (t1/2) was 24.1 +/- 5.7 hours and of volume of distribution/bioavailability 1.2 +/- 0.12 L/kg. Saliva conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
152
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(171 citation statements)
references
References 7 publications
15
152
1
3
Order By: Relevance
“…Including the quantitative TBW covariate, LTG CL in the final model proposed was 0.039 L·h -1 ·kg -1 , which is higher than the values of approximately 0.021 to 0.035 L·h -1 ·kg -1 that were reported in PK studies evaluating small numbers of adult patients and healthy adult volunteers using standard approaches (2-stage methods with a 1-compartment model) [8][9][10]24] . Our study has shown a nonlinear increase of the CL and V d of LTG with an increase in total body weight.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Including the quantitative TBW covariate, LTG CL in the final model proposed was 0.039 L·h -1 ·kg -1 , which is higher than the values of approximately 0.021 to 0.035 L·h -1 ·kg -1 that were reported in PK studies evaluating small numbers of adult patients and healthy adult volunteers using standard approaches (2-stage methods with a 1-compartment model) [8][9][10]24] . Our study has shown a nonlinear increase of the CL and V d of LTG with an increase in total body weight.…”
Section: Discussionmentioning
confidence: 97%
“…The traditional method for calculating individual PK parameters was to collect multiple (up to [7][8][9][10] blood samples from a single patient at different times after a single dose. This method was not always accepted by patients, especially children.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Two reports indicate that induction of glucuronidation pathways by oxcarbazepine may affect the metabolism of lamotrigine (May et al, 1999;Kramer et al, 2003) and another describes higher MHD concentrations in the presence of lamotrigine compared to oxcarbazepine monotherapy (Guenault et al, 2003). Drug interactions may also be theoretically possible due to the potential inhibition of glucuronidation, which is the first-step of the metabolism and excretion pathway of the active metabolite of oxcarbazepine 10-monohydroxy (MHD) (May et al, 2003) as well as the most important metabolic transformation inactivating lamotrigine (Cohen et al, 1987;Lloyd et al, 1994).…”
Section: Lamotriginementioning
confidence: 99%
“…According to a randomisation code, 12 subjects received either lamotrigine 300 mg or lactose placebo given as matching capsules. The intranasal CO 2 test was performed again 2 h after treatment to coincide approximately with peak plasma lamotrigine concentrations [8]. There was an interval of at least 2 weeks between treatments.…”
Section: Methodsmentioning
confidence: 99%